Simultaneous enhancement of piezoelectric performance and Curie temperature in high-temperature Bi4Ti3O12 piezoceramics through A/B site co-doping - Xuanyu Chen; Bao Ou; Guanfu Liu; Yuxing Dai; Bin Li; Yejing Dai (Journal of Advanced Ceramics, 2025)
For Bi4Ti3O12 (BIT) high-temperature piezoceramics, improving piezoelectric performance often comes at the expense of a reduced Curie temperature. In this study, a series of Bi4−xCexTi2.97(Cr1/3Ta2/3)0.03O12 (x = 0, 0.02, 0.04, 0.06, and 0.08) ceramics were synthesized using the solid-state reaction method, and their phase structure, microstructure, piezoelectric properties, and conduction mechanisms were systematically analyzed. By employing a B-site non-equivalent co-doping strategy and introducing Ce ions into the A-site, we achieve a synergistic increase in the piezoelectric performance, Curie temperature, and high-temperature resistivity of BIT-based ceramics. This A/B site multi-co-doping significantly enhances the electrical properties by reducing the oxygen vacancy concentration. Notably, the ceramics with x = 0.04 exhibit a high piezoelectric coefficient (d33) of 37 pC·N−1, excellent resistivity of 6.6×106 Ω·cm at 500 °C, and a high Curie temperature of 681 °C. Piezoelectric force microscopy and phase field simulation reveal that the superior piezoelectric performance arises from larger domain sizes, a stronger response to external electric fields, and a higher breakdown field strength. These findings not only position this material as a robust candidate for high-temperature applications but also provide valuable insights into the design of piezoelectric ceramics with enhanced stability and performance.